PENGARUH ARAH SERAT TERHADAP FAKTOR INTENSITAS TEGANGAN PADA UNIDIRECTIONAL LAMINA YANG MENGANDUNG CENTER CRACK - IGN Wiratmaja Puja; Yedi R Supriyadi (Mesin, 2000)
This paper presents the stress intensity factor (SIF) analysis for unidirectional ï¬ber-matrix lamina containing center crack under uniaxial loading. Several variables are considered on the inï¬‚uence to the stress intensiï¬cation factor i.e. ï¬ber direction,Î¸, crack dimension parameter, 2a/L, ï¬ber and matrix volume fraction, Vf, Vm, ï¬ber and matrix stiffness ration, Ef/Em, and lamina thickness. The stress-strain equations for the lamina are derived using micromechanic approach. The governing equations are solved numerically using the finite element method with triangular type element. The element stiï¬ness matrix is obtained using the polynomial shape functions. The software to calculate stress-strain in the lamina containing center crack is developed. Case studies jor numerical purposes consider the carbon-epoagz lamina with carbon type P-100. Numerical results for carbon epoxy lamina are presented in graphical form of SIF as a ï¬mction of the ï¬ber direction, ï¬ber matrix stiï¬hess ratio and volume ratio, and crack geometry.